4R Research With Impact. Issue 1 (22nd December 2022) - Bruulsema, Tom
Abstract: In 2013, the fertilizer industry in North America launched the 4R Research Fund. Members of the fertilizer industry pledged annual commitments of financial support to research connecting 4R practices to impacts. This article briefly summarizes findings and benefits to the industry that have resulted from the financial support directed towards research. Earn 0.5 CEUs in Nutrient Management by reading this article and taking the quiz at https://web.sciencesocieties.org/Learning‐Center/Courses.